A comparative cluster analysis of nicotinamide adenine dinucleotide phosphate (NADPH)‐diaphorase histochemistry in the brains of amphibians. Issue 13 (3rd April 2014) - Pinelli, Claudia; Rastogi, Rakesh K.; Scandurra, Anna; Jadhao, Arun G.; Aria, Massimo; D'Aniello, Biagio
ABSTRACT Nicotinamide adenine dinucleotide phosphate–diaphorase (NADPH‐d) is a key enzyme in the synthesis of the gaseous neurotransmitter nitric oxide. We compare the distribution of NADPH‐d in the brain of four species of hylid frogs. NADPH‐d–positive fibers are present throughout much of the brain, whereas stained cell groups are distributed in well‐defined regions. Whereas most brain areas consistently show positive neurons in all species, in some areas species‐specific differences occur. We analyzed our data and those available for other amphibian species to build a matrix on NADPH‐d brain distribution for a multivariate analysis. Brain dissimilarities were quantified by using the Jaccard index in a hierarchical clustering procedure. The whole brain dendrogram was compared with that of its main subdivisions by applying the Fowlkes–Mallows index for dendrogram similarity, followed by bootstrap replications and a permutation test. Despite the differences in the distribution map of the NADPH‐d system among species, cluster analysis of data from the whole brain and hindbrain faithfully reflected the evolutionary history (framework) of amphibians. Dendrograms from the secondary prosencephalon, diencephalon, mesencephalon, and isthmus showed some deviation from the main scheme. Thus, the present analysis supports the major evolutionary stability of the hindbrain. We provide evidence that the NADPH‐d system in main brain subdivisions should be cautiously approached for comparative purposes because specific adaptations of a single species could occur and may affect the NADPH‐d distribution pattern in a brain subdivision. The minor differences in staining pattern of particular subdivisions apparently do not affect the general patterns of staining across species. J. Comp. Neurol. 522:2980–3003, 2014. © 2014 Wiley Periodicals, Inc.